Introduction to the Russo-Japanese revolution in stabilometry - Gagey, Pierre-Marie (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
We knew that the postural system was concerned with the venous return circulation and the stabilization of the body, but we did not know that the stabilometric signal was modified by the interference of these two functions. A new signal analysis is being made.